2020
DOI: 10.1016/j.jpain.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of Cannabis on Headache and Migraine

Abstract: Use of cannabis to alleviate headache and migraine is relatively common, yet research on its effectiveness remains sparse. We sought to determine whether inhalation of cannabis decreases headache and migraine ratings as well as whether gender, type of cannabis (concentrate vs flower), delta-9-tetrahydrocannabinol, cannabidiol, or dose contribute to changes in these ratings. Finally, we explored evidence for tolerance to these effects. Archival data were obtained from Strainprint, a medical cannabis app that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…We divided our sample into non-responders (i.e., <50%; n = 56, 39%) and responders (i.e., ≥50%; responders n = 89, 61%) based on their reduction of monthly frequency of migraine attacks from pre-MC to the current post-MC period. No significant difference was found in monthly migraine attack frequency prior to MC treatment initiation (15 (7.8-30) and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), respectively) (0.06 95% CI (−0.27 to 0.41); p = 0.71), strengthening the division methodology, as both subgroups started from a similar standpoint. Moreover, there were no significant differences between the subgroups in any of the current migraine features, including the age of migraine diagnosis, average duration of migraine attacks, activity-induced aggravation of migraine, unilateral migraine, bilateral migraine, presence of aura prior to migraine, nausea during migraine, or phono-or photophobia during migraine (Table 2).…”
Section: Migraine and Sleep Featuresmentioning
confidence: 78%
See 1 more Smart Citation
“…We divided our sample into non-responders (i.e., <50%; n = 56, 39%) and responders (i.e., ≥50%; responders n = 89, 61%) based on their reduction of monthly frequency of migraine attacks from pre-MC to the current post-MC period. No significant difference was found in monthly migraine attack frequency prior to MC treatment initiation (15 (7.8-30) and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), respectively) (0.06 95% CI (−0.27 to 0.41); p = 0.71), strengthening the division methodology, as both subgroups started from a similar standpoint. Moreover, there were no significant differences between the subgroups in any of the current migraine features, including the age of migraine diagnosis, average duration of migraine attacks, activity-induced aggravation of migraine, unilateral migraine, bilateral migraine, presence of aura prior to migraine, nausea during migraine, or phono-or photophobia during migraine (Table 2).…”
Section: Migraine and Sleep Featuresmentioning
confidence: 78%
“…A recent cross-sectional study found that nearly 36% of MC users reported using it to treat headache and migraine [9]. An additional survey reported about 50% reduction of migraine and headache severity following inhaled cannabis consumption [10]. Nevertheless, good clinical data supporting the beneficial effect of MC on migraine are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…35 Our data on dosage of cannabis and changes in dosage over time are also consistent with other studies. 12,36 We found overall increases in dosage and effectiveness score over time for participants treating pain symptoms. Changes in cannabis dosage over time varied by effectiveness score, suggesting that participants titrated dosages based on perceived effectiveness.…”
Section: Medical Cannabis Users: Products and Insightsmentioning
confidence: 84%
“…7,8 Several studies have observed that medical cannabis may have therapeutic benefit in patients with headache (including migraine), gastrointestinal pain, arthritis, and joint stiffness. 3,6,[9][10][11][12][13][14][15] However, randomized controlled trials (RCTs) are often too small and too short to draw definitive conclusions. 16 In addition, studies use different cannabinoid preparations and modes of administration, making meta-analyses complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite perceived efficacy often reported by medicinal and recreational cannabis users across a range of psychological and physiological symptoms [12,13,70] , a growing empirical corpus supports the supposition that users experience worse pain outcomes when compared to non-users [9,17,40,41,49,68,76,77] . In one seminal study involving patients without chronic pain histories [41] , researchers tracked adults undergoing elective orthopedic operations during the postoperative period.…”
Section: Recreational Cannabis Is Associated With Worse Pain Outcomesmentioning
confidence: 99%